(untitled) (Pesquisa Odontológica Brasileira, 2003)
The aim of this study was to evaluate the influence of storage periods of 24 hours and 3 months on the microleakage of class II cavities. Two methods of assessing microleakage were also compared. Class II cavities were prepared in sound human molars. MO cavities were restored using ABF experimental (Kuraray Medical Inc.) + Z250 composite resin (3M ESPE), and DO cavities were restored using Single Bond (3M ESPE) + Z250. After different storage periods, specimens were thermocycled, immersed in a dye (0.5% methylene blue solution for 4 h) and longitudinally sectioned. Dye penetration was scored according to a 0-4 scale. The extent of microleakage was measured using the ImageLab 2000 program. A statistically significant correlation was verified between both evaluation methods (r = 0.978, p < 0.001). ANOVA revealed a statistically significant difference between the tested adhesive systems regarding microleakage (p < 0.001), although it was not influenced by the different storage periods.